Withholding treatment from disabled newborns and its effect on the right to life in Nigeria (2010)
The ultimate aim of medical treatment is to provide benefit for the patient and such treatment should not be prolonged if it cannot achieve this aim. Remarkable advances in neonatal care now make it possible to sustain the lives of many newborn infants who several years ago would have died in the first days or weeks after birth. Not all newborns fare well. Some infants with low birth weight or severe defects cannot survive for long, despite the most aggressive efforts to save them; others suffer severe impairments either as a component of their conditions or as a result of treatments. Consequently, medicine’s increased ability to forestall death in seriously ill-newborns and this has magnified the already difficult task of physicians and parents who must attempt to assess which infants may or may not benefit from various medical interventions. This paper will examine the legal implications of withholding treatment in such instances. This will include the right of the child (with particular reference to the right to life) and whether this right is absolute. The paper will also discuss the grounds for state intervention in protecting the rights of a child. In doing this, the Baby Doe incidence which occurred in the United States of America will be used as a case study. An outcome of the Baby Doe case in the USA is the Baby Doe Law, and as such, this paper will also discuss the provisions of this law. It will also look at the provisions of the Nigerian Law in respect of withholding treatment for disabled newborns to determine whether or not the law on this issue is adequate